2018
DOI: 10.1038/s41598-018-22735-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into positive and negative allosteric regulation of a G protein-coupled receptor through protein-lipid interactions

Abstract: Lipids are becoming known as essential allosteric modulators of G protein-coupled receptor (GPCRs). However, how they exert their effects on GPCR conformation at the atomic level is still unclear. In light of recent experimental data, we have performed several long-timescale molecular dynamics (MD) simulations, totalling 24 μs, to rigorously map allosteric modulation and conformational changes in the β2 adrenergic receptor (β2AR) that occur as a result of interactions with three different phospholipids. In par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 78 publications
(177 reference statements)
12
55
0
Order By: Relevance
“…This was consistent with another study favored partial deactivation of the b2AR was found in the 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) lipids (27). In coarse-grained MD simulations, Song et.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…This was consistent with another study favored partial deactivation of the b2AR was found in the 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) lipids (27). In coarse-grained MD simulations, Song et.…”
Section: Introductionsupporting
confidence: 90%
“…The only positive correlation between the transmembrane helices and the lipids was observed between the intracellular region of TM6 and lipids in the lower leaflet of active A1AR. Four lysine residues (K263 6.25 , K267 6.29 , K270 6.32 and K273 6.35 ) present in the intracellular end in the b2AR of TM6 were also known to interact with negatively-charged headgroups of 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE) lipid molecules in and thus stabilize the GPCR active state (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the role of lipids in activation of Class B1 GPCRs is less well understood. Whilst the activation of Class A GPCRs is modulated by membrane lipids (14)(15)(16) which may act as allosteric regulators of GPCR activity (15,17,18), the interactions of lipids with Class B GPCRs have not been extensively characterised.…”
Section: Introductionmentioning
confidence: 99%